2020
DOI: 10.3389/fcimb.2020.00350
|View full text |Cite
|
Sign up to set email alerts
|

Structural Variations of Vaginal and Endometrial Microbiota: Hints on Female Infertility

Abstract: Microbiota are microorganismal communities colonizing human tissues exposed to the external environment, including the urogenital tract. The bacterial composition of the vaginal microbiota has been established and is partially related to obstetric outcome, while the uterine microbiota, considered to be a sterile environment for years, is now the focus of more extensive studies and debates. The characterization of the microbiota contained in the reproductive tract (RT) of asymptomatic and infertile women, could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 66 publications
(90 reference statements)
1
70
0
1
Order By: Relevance
“…In infancy, n (%) 4 (29) 19 (90) 14 (61) <0.001 3 In adulthood, n (%) 4 (29) 16 (76) 19 (83) 0.003 3…”
Section: Antibiotic Usagementioning
confidence: 99%
See 2 more Smart Citations
“…In infancy, n (%) 4 (29) 19 (90) 14 (61) <0.001 3 In adulthood, n (%) 4 (29) 16 (76) 19 (83) 0.003 3…”
Section: Antibiotic Usagementioning
confidence: 99%
“…Metataxonomic studies of endometrial samples have also revealed that an abnormal endometrial bacterial profile (with a low percentage of sequences of the genus Lactobacillus) is a common feature in a high percentage of infertile women subjected to ART [21,29]. Although at least a part of the bacterial DNA detected in endometrial samples may arise from vaginal contamination during sampling, these studies suggest that an abundant presence of Lactobacillus DNA in such samples may be a predictor of implantation success [29,30].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The impact of the genital tract microbiome on human reproductive physiology is widely studied [ 1 , 2 , 3 , 4 , 5 ]. The disclosure of the role of the female and male urogenital microorganisms in the onset of pregnancy may lead to the identification of new predictive markers of reproductive fitness.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, in a very recent study, the samples were taken with a particular method based on the combined use of two specific catheters and accurate tissue disinfection; thus, the procedure could be considered almost sterile. The absent contamination by the vaginal flora, as a result, highlighted a characteristic heterogeneous endometrial microbiota (also including newly identified genital bacteria such as Kocuria dechangensis and the absence of Lactobacilli) different from the vaginal one (dominated by the Lactobacillus genus) [ 62 ]. Although interesting, these results should be confirmed in future studies based on the same sampling technique.…”
Section: Female Tract Microbiotamentioning
confidence: 99%